PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS MIND MAPPING PADA MATERI SISTEM PEREDARAN DARAH SMA - Maria Febria Orkha; Diah Putri Anggun; Indah Wigati (Bioilmi: Jurnal Pendidikan, 2020)
The learning module is one of the learning materials that makes students learn independently so that is known to what extent students have mastered a learning material. Based on the analysis of needs at SMA Nurul Qomar Palembang, it is known that the condition of the learning module is still a learning module with material presentation in the form of essays which are still equipped with writing without a certain approach, so that students find it difficult to understand the material. This study aims to determine the validty and practicality of mind mapping learning modules on the circulatory system material for SMA Nurul Qomar Palembang. This research is up to the seventh stage of ten stages, namely: 1)potential and problems, 2)data collection, 3)product design,4)design validation, 5)design revision, 6)product testing, 7) product revision. The subjects of this study were students of class XI IPA SMA Nurul Qomar Palembang. The data collection techniques used were observation, interview and questionnaire distribution. The data analysis technique used is the analysis of the validty of the learning module and the analysis of the practicality of the learning module with a measurement scae according to Riduwan (2009). Based on the validation of several experts 90,62%, and learning device experts 83,33%, biology teacher response 75,59%, student response 88,21%, the mind mapping learning module on the high school blood circulation system material gets the criteria of “Very Appropriate” so it is very well usedin the learning process. Keywords : Module , Mind Mapping , Learning Material